2015
DOI: 10.1016/j.paid.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Gray’s revised Reinforcement Sensitivity Theory in relation to Attention-Deficit/Hyperactivity and Tourette-like behaviors in the general population

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Abstract Attention-Deficit/Hyperactivity Disorder (ADHD) and Tourette Syndrome (TS) present as distinct conditions clinically; however, they show comorbidity and inhibitory control defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In addition to achievement motivation, there is also evidence showing the scale also measures hyperactive and impulsive behavior (e.g., Gomez and Corr Heym et al 2015). Thus it may be that the ASD performance reflects impulsivity rather than memory deficits.…”
Section: Foilmentioning
confidence: 99%
“…In addition to achievement motivation, there is also evidence showing the scale also measures hyperactive and impulsive behavior (e.g., Gomez and Corr Heym et al 2015). Thus it may be that the ASD performance reflects impulsivity rather than memory deficits.…”
Section: Foilmentioning
confidence: 99%
“…Findings with regard to hyperactivity/impulsivity are less consistent as it has been associated with higher and lower levels of BAS (Gomez & Corr, 2010;Heym et al, 2015), but also higher and lower levels of BIS (Heym et al, 2015;Hundt et al, 2008;Mitchell & Nelson-Gray, 2006). In addition, there is some evidence for a link between hyperactivity/impulsivity and increased FFFS (Heym et al, 2015). The measure of response modulation, in the approach-avoidance paradigm, is derived by comparing a condition where participants are instructed to approach positive and avoid negative emotional stimuli (congruent condition) and one where the instruction is to avoid positive and approach negative emotional stimuli (incongruent condition).…”
Section: Introductionmentioning
confidence: 91%
“…The behavioral inhibition system (BIS) is activated in the presence of conflicting cues, giving rise to inhibition of ongoing behavior (Gray & McNaughton, 2000). It OVERRIDDING APPROACH-AVOIDANCE TENDENCIES IN ADHD 6 has been reported that symptoms of inattention in ADHD are underpinned by an overactive BIS (Gomez & Corr, 2010;Heym, Kantini, Checkley, & Cassaday, 2015;Hundt, Kimbrel, Mitchell, & Nelson-Gray, 2008;Mitchell & Nelson-Gray, 2006). Findings with regard to hyperactivity/impulsivity are less consistent as it has been associated with higher and lower levels of BAS (Gomez & Corr, 2010;Heym et al, 2015), but also higher and lower levels of BIS (Heym et al, 2015;Hundt et al, 2008;Mitchell & Nelson-Gray, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the role of BIS and BAS might be very important during adolescence given that reward processing peaks during this developmental age period whereas inhibitory capacities are generally lower compared to other age groups ( Galván, 2013 ; Romer & Hennessy, 2007 ). Furthermore, variations in BIS and BAS sensitivity can explain individual differences in personality and psychopathology (e.g., Harrison, Treasure, & Smillie, 2011 ; Heym, Kantini, Checkley, & Cassaday, 2015 ; Soler et al, 2014 ). Two studies report findings concerning the factor structure of the BIS/BAS Scales in adolescent samples ( Cooper, Gomez, & Aucote, 2007 ; Yu, Branje, Keijsers, & Meeus, 2011 ) with Cooper et al ( 2007 ) finding evidence for a four-factor model in an Australian population, whereas Yu et al ( 2011 ) found evidence for a two-factor model in a Dutch population.…”
Section: Introductionmentioning
confidence: 99%